Analyzing the Impact of Science Practicum on Sixth-Grade Students' Cognitive Development - Sri Darmayanti, Ni Wayan; Sari Devi, Ni Luh Ketut Jenutri; Sanjayanti, Ni Putu Ayu Hervina; Janawati, Desak Putu Anom (Jurnal Inovasi Pendidikan dan Sains, 2025)
This study aims to analyze the implications of science practicum learning on the cognitive development of sixth-grade students at SD Negeri 5 Nongan. This study employs a descriptive qualitative research design and was conducted at SD Negeri 5 Nongan. The subjects of this research were one teacher and 15 sixth-grade students. Data collection methods used interviews, and the instrument was an interview sheet. Data analysis techniques utilized a descriptive statistical analysis approach. The results of this study indicate that science practicum learning for sixth-grade students at SD Negeri 5 Nongan has been implemented routinely and effectively. The science practicum has proven to be an effective learning method in improving students' understanding, skills, motivation, and learning outcomes. In this context, the teacher acts as a facilitator, in alignment with the Merdeka Curriculum. The science practicum provides an interactive, hands-on learning experience, helping students deeply comprehend concepts while enhancing their critical and analytical thinking skills. Based on these findings, it is recommended that teachers use science practicums employing simple and easily understood media, such as the surrounding environment and tangible objects, as learning tools for science practicums. This approach is expected to make science practicums more effective and engaging for students